2014
DOI: 10.1101/gad.236794.113
|View full text |Cite
|
Sign up to set email alerts
|

The methyltransferase G9a regulates HoxA9-dependent transcription in AML

Abstract: Chromatin modulators are emerging as attractive drug targets, given their widespread implication in human cancers and susceptibility to pharmacological inhibition. Here we establish the histone methyltransferase G9a/ EHMT2 as a selective regulator of fast proliferating myeloid progenitors with no discernible function in hematopoietic stem cells (HSCs). In mouse models of acute myeloid leukemia (AML), loss of G9a significantly delays disease progression and reduces leukemia stem cell (LSC) frequency. We connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
147
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 43 publications
0
147
0
Order By: Relevance
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…Unmodified H3 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] peptide (23 μM) was incubated with 25 nM G9a-SET in the presence of 50 μM SAM (radioactive: nonradioactive molar ratio = 0.016) in a buffer containing 50 mM Hepes (pH 7.9), 0.5 mM DTT, 0.25 mM PMSF, and 2 mM MgCl 2 . Where applicable, different H3 1-20 K9X peptides (Tufts University Peptide Synthesis Core) were present in the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies identified a role for G9a in heterochromatin maintenance and transcriptional repression, such as the silencing of repeat elements, including long interspersed nuclear elements and endogenous retroviruses (12)(13)(14). Up-regulation of both G9a and G9a like protein (GLP) has implications in a variety of human cancers, including solid tumors as well as acute myeloid leukemia (15)(16)(17). Here, we present biochemical and structural evidence that the histone H3K9M peptide inhibits G9a activity by effectively competing with WT histone H3 substrate peptide for binding to the active site.…”
mentioning
confidence: 99%
“…The evidence that in mouse models of acute myeloid leukemia, loss of G9a significantly delays disease progression and reduces leukemia stem cell frequency (69) provides further evidence of a tumorigenic role of elevated levels of G9a. Interestingly, G9a has been recently shown to sustain cancer cell survival and proliferation by transcriptional activation, through deposition of H3K9me1, of the serine-glycine biosynthetic pathway (32).…”
Section: Cancermentioning
confidence: 97%